Crystal structure of dibromo-dicarbonyl-bis(tricyclohexylphosphine)-osmium(II) dichloromethane solvate, C38H66Br2O2OsP2 - Monareng Jubrey M.; Clayton Hadley S. (Zeitschrift für Kristallographie - New Crystal Structures)
C38H66Br2O2OsP2, triclinic, P1‾ $P\overline{1}$ (no. 2), a = 10.4091(2) Å, b = 10.6868(2) Å, c = 21.3533(4) Å, α = 84.658(1)°, β = 89.764(1)°, γ = 64.918(1)°, V = 2140.36(7) Å3, Z = 2, R gt(F) = 0.0248, wR ref(F 2) = 0.0578, T = 173(2) K.